Poland-Möbius syndrome: a case report implicating a novel mutation of the PLXND1 gene and literature review - Graeme E. Glass; Shiyas Mohammedali; Bran Sivakumar; Mitchell A. Stotland; Faisal Abdulkader; Debra O. Prosser; Donald R. Love (BMC, 2022)
Abstract Background Möbius (Moebius) and Poland's syndromes are two rare congenital syndromes characterized by non-progressive bilateral (and often asymmetric) dysfunction of the 6th and 7th cranial nerves and hypoplasia of the pectoral muscles associated with chest wall and upper limb anomalies respectively. Manifest simultaneously as Poland-Möbius (Poland-Moebius) syndrome, debate continues as to whether this is a distinct nosological entity or represents phenotypic variation as part of a spectrum of disorders of rhomboencephalic development. Etiological hypotheses implicate both genetic and environmental factors. The PLXND1 gene codes for a protein expressed in the fetal central nervous system and vascular endothelium and is thus involved in embryonic neurogenesis and vasculogenesis. It is located at chromosome region 3q21-q22, a locus of interest for Möbius syndrome. Case presentation We present the first report of a patient with Poland-Möbius syndrome and a mutation in the PLXND1 gene. A child with Poland-Möbius syndrome and a maternally inherited missense variant (NM_015103.2:ex14:c.2890G > Ap.V964M) in the PLXND1 gene is described. In order to contextualize these findings, the literature was examined to identify other confirmed cases of Poland-Möbius syndrome for which genetic data were available. Fourteen additional cases of Poland-Möbius syndrome with genetic studies are described in the literature. None implicated the PLXND1 gene which has previously been implicated in isolated Möbius syndrome. Conclusions This report provides further evidence in support of a role for PLXND1 mutations in Möbius syndrome and reasserts the nosological link between Möbius and Poland's syndromes. Level of evidence Level V, Descriptive Study.